CLONING DETECTION ON THE BASE OF TEXTUAL SIMILARITY USING NEURAL AS A CLASSIFIER - Kaur, Kulbir; Singh, Rasbir (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Cloning refer to copying the data from one place and using it on another place. This particular work has made the task of the developers easy as it is often that the developers copy the content of one work and paste it into another but this particular procedure violets the rule of copyrights. Copying data is feasible upto one extent but copying entire data set or data or code from one place to another is a serious issue .This paper focuses on the introduction of the code cloning and data cloning and the ways to prevent the cloning.